A dual generalization of convex functions - M. Apetrii (Journal of Numerical Analysis and Approximation Theory, 2007)
As it is well known, the convexity property of a function may be described by the quasiconvexity property of all "the dual perturbations" of this function. If we consider the "dual perturbation" only in a subset \(M\subset X^{*}\) we obtain a general class of functions called \(M\)-convex. In this paper we establish some special properties and a continuity theorem of this new type of functions.